The Effectiveness of Google Classroom in Teaching Writing of Recount Text for Senior High Schools - Laili, Ela Nur; Muflihah, Tatik (JOLLT Journal of Languages and Language Teaching, 2020)
This research aimed to find out Google Classroom effectiveness, which was used to enhance studentsâ€™ writing recount text for Senior High School and recognize students’ writing performance. This research used a pre-experimental research design. The subject of this study is the tenth grade of senior high school at Western Surabaya. It involved 30 students as a sample of this study. In the process of data collection, the researcher used a pre-test, post-test, and questionnaire. The researcher analyzed the data using Wilcoxon Ranks Test to test the hypothesis. This study found the value of significance (2-tailed) was lower than the significance level (0.022 < 0.05), then the Ha was accepted. It means there was a significant value on studentsâ€™ achievement of the writing performance of recount text by using Google Classroom. In addition, the result of the questionnaire indicates that the studentsâ€™ responses are neutral; it means that the students do not feel difficult in the use of Google Classroom. However, it can be concluded that Google Classroom significantly affects studentsâ€™ writing performance and helps them finish and collect the assignment without any bound by time and space. Further, based on the data obtained, which analyzed through Brown’s theory, the students’ writing performance is imitative and intensive. It means they are still positioning in the primary category.